Rasesynet hos mormonerne i det forrige århundre - Glad, Johnnie (Religionsvidenskabeligt Tidsskrift, 1991)
The Church of Jesus Christ of Latter-Day Saints (also known as the Mormon Church) was established on April 6, 1830, by Joseph Smith, Jr. in Fayette, New York. The Mormon Church claims to be not only a Christian church, but also the only true church here on earth. In addition to the Bible, this church has several authoritative sacred scriptures, such as the Book of Mormon, Doctrine and Covenants, and the Pearl of Great Price. One of the issues that has haunted the Mormon Church down through the years and caused considerable embarrassment and unrest, has been the race issue. Why were Negroes prohibited from entering the priesthood? Why were the Indians and the Negroes stigmatized? Why should a white skin be considered better and more favourable than a dark skin? The intention of this article is to throw some light on this issue and see how it developed during the previous century. It is important in this context to examine the Mormon scriptures. What did they have to say about this issue? And what about the church leaders? How did they look upon and tackle these problems? The leaders of the church had great authority and power. What they said and did had far-reaching consequences in the church and created a pattern for other to follow. The following century is a case in point.